Patterns for translation of compound nouns in the Russian, English, and German languages - T.K. Ivanova; N.V. Arzhantseva; I.V. Erofeeva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper deals with the methodological patterns for translation of compound nouns in the Russian, English, and German languages. The novelty of the research is determined by the fact that the epoch of rapidly developing public and academic interactions between countries is marked both by a significant increase in the number of compound words in the Russian language which require adequate translation and by the insufficient research on Russian, and English, German compound nouns. The purpose of the current study is to investigate regular and irregular equivalents to Russian compound nouns. The purpose has been fulfilled using the following methods: comparative and descriptive methods, as well as the method of structural and semantic analysis based on the onomasiological approach. Our attention has been focused on the structural and semantic characteristics of compound nouns and transformations which help to achieve a high degree of equivalence between Russian, English, and German compounds. As a result of the linguistic analysis, two groups of compound nouns have been singled out. The article provides numerous examples proving that the two groups have regular translation equivalents functioning as compound nouns and/or word combinations. To improve understanding of the patterns, the structural and semantic equivalents of the most common word-building models have been presented as tables. The results of the study bring us to the following conclusions: interlingual equivalents to compound nouns might be interlevel and intercapable phenomena of the language system in general. Russian compound nouns have equivalents among German and English nouns or, more rarely, periphrases as equivalents, while German and English compound nouns are most commonly translated into Russian as descriptive phrases or attributive word groups, which can be explained by their less frequent usage in the language. Besides, compounds can have different equivalents depending on the context.